A porous hydrogel-electrospun composite scaffold made of oxidized alginate/gelatin/silk fibroin for tissue engineering application. (1st October 2020) - Hajiabbas, Maryam; Alemzadeh, Iran; Vossoughi, Manouchehr
Highlights: Fabrication of nanofibrous hydrogel made of oxidized alginate/gelatin/silk fibroin. Evaluation of the structure-property relationship in prepared scaffolds. Fabrication of 3D silk fibroin electrospun and engineering extracellular structure. Evaluation of the composition-property relationship in prepared scaffolds. Investigation of the stem cell-scaffold interaction. Abstract: In the article, a bilayer nanocomposite scaffold made of oxidized alginate (OAL), gelatin (G), and silk fibroin (SF) has been prepared via combining electrospinning, in situ gas foaming, in situ crosslinking and freeze drying methods. The physicochemical and mechanical properties, as well as thermal stability of the proposed composite, have been investigated by SEM, FTIR, XRD, tensile, and TGA analysis. The data indicate that structure and degree of crosslinking play a vital role in adjusting the physical and mechanical properties of composite scaffolds. Further, the authors find a favorable adipose-derived mesenchymal stem cell's (AMSC) attachment and distribution within this novel hydrogel-electrospun composite. Such a nanocomposite structure with its promising properties and cell-material interaction may be considered as a new scaffold for different tissue engineering applications.